Study on the behavior of monopiles used to founding offshore wind turbines (Latakia University Journal -Engineering Sciences Series, 2024)
Horizontally loaded piles used in founding electric power generation fans are affected bywind forces and repeated wave loads applied to them. This research is a computermodeling and analytical study of a loaded monopile pile which is used as a foundation fora offshore wind turbine fixed in a medium compacted and compacted sandy soil (seabed). In this research is Hardening Soil model (HS) used for the soil surrounding the pile.The horizontal displacement values are determined due to several parameters. It is shownthat the horizontal displacement of the monoopile is controlled by several parameterssuch as: its embedded length, its diameter, the height of the sea water, the value of thetotal horizontal force and its arm Calculations show that cyclic loading increases thehorizontal displacement by 30%, and that the soil subgrade reaction coefficientdistribution.with depth is not linear in sandy soil and Rees’ method for calculatinghorizontally loaded piles is not very suitable for monopile piles, especially in thedisplacement and moment distribution diagrams .